Peritraumatic distress and its association with resilience among a sample of war-exposed Palestinian population: a cross-sectional study - Suheir S. Sabbah; Hamzeh Yacoub; Rita Yacoub; Zaid Yacoub; Khalil Sabbah; Yousef B. Ghannam (Middle East Current Psychiatry)
Abstract Background War is an intense traumatic experience that can result in severe psychological distress. Peritraumatic distress (PTD) refers to the emotional and psychological response experienced during or immediately after trauma and is a known predictor of posttraumatic stress disorder (PTSD). Resilience has an important role in coping with trauma-related distress, reducing its intensity, and promoting recovery. Understanding the relationship between PTD and resilience is essential for developing effective mental health interventions in war-affected populations. Objective This study aimed to explore the association between PTD and resilience among a developing population exposed to war-related trauma and to explore the influence of sociodemographic and health-related factors on these psychological responses. Method A cross-sectional study was conducted among 660 Palestinian adults exposed to war-related trauma. Participants completed validated Arabic versions of the Peritraumatic Distress Inventory (PDI) and the Connor-Davidson Resilience Scale (CD-RISC-10). Statistical analyses included descriptive statistics, Pearson correlations, and linear regression models. Results Participants reported moderate PTD levels (Mean = 36.1, SD = 9.00), with 16.5% scoring high levels. Resilience scores were also moderate (Mean = 32.35, SD = 9.00), with nearly half (49.7%) scoring in the high range. Higher PTD was significantly associated with higher resilience (B = 0.3, β = 0.301, p < 0.001), a finding that may reflect adaptive coping processes in highly stressful environments. Additional predictors of resilience included age, educational level, employment status, and health condition. Conclusion Our findings suggest a significant relationship between PTD and resilience, suggesting that PTD may activate adaptive coping mechanisms during war-related trauma. The study also emphasizes the need for early mental health interventions, resilience-building programs, and targeted support in war-affected regions to control long-term psychological consequences.